System Requirement Analysis and User Interface Design for Information Systems Using a Collaborative Approach of Agile and User-Centered Design Methods - Marcho Oknivan Tumbade; Waiki Elkius Kogoya; Gasper Tabuni; Yohanes Tabuni (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The rapid acceleration and advancement of information technology have significantly impacted the education sector, including higher education institutions. However, the implementation of existing systems has also introduced new challenges that are not yet addressed within the digitalization of information systems. One such issue is the absence of a dedicated platform for Student Online Complaint Services. This includes the lack of digital records as evidence and archives of complaints and issues raised by students, and the establishment of task forces such as the PPKS (Prevention and Handling of Sexual Violence). Despite these efforts, there is no digital-based platform to facilitate online complaints. The objective of this research is to develop a requirement model and user interface design to support the design of a web-based system that serves as a platform for students to easily report issues encountered during their studies. It also aims to assist campus stakeholders in capturing all student complaints as documentation for internal evaluation. The methodology used includes Agile Development Requirements Engineering with the Scrum model and the User-Centered Design (UCD) method to address the identified issues and research objectives. The research outcomes include the development stages of the website, system requirements, requirement model processes, requirement specification, and user interface design. furthermore, the research tested the user interface design on a website prototype, achieving a score of 87.5, classified as Excellent under the Adjective Rating system.